Çöz (x + 1) (x + 3) (x + 4) (x + 6) = 112?

Çöz (x + 1) (x + 3) (x + 4) (x + 6) = 112?
Anonim

Cevap:

#, X = -7/2 + -isqrt31 / 2 # veya #, X = -7/2 + -sqrt57 / 2 #

Açıklama:

LHS'yi şu şekilde gruplayalım:

# (X + 1) (x + 6) (x + 3) (x + 4) = 112 #

# => (X ^ 2 + 7x + 6) (x ^ 2 + 7x + 12) = 112 #

Şimdi izin ver # U = x ^ 2 + 7x # ve sonra yukarıdaki denklem olur

# (U + 6) (u + 12) = 112 #

veya # U ^ 2 + 18U + 72 = 112 #

veya # U ^ 2 + 18U-40 = 0 #

veya # I (u + 20) ı (u-2) = 0 # diğer bir deyişle # U = 2 # veya #-20#

Ya da # X, ^ 2 + 7x + 20 = 0 # diğer bir deyişle # x = (- 7 + -sqrt (7 ^ 2-80)) / 2 # diğer bir deyişle #, X = -7/2 + -isqrt31 / 2 #

veya # X, ^ 2 + 7x-2 = 0 # diğer bir deyişle # x = (- 7 + -sqrt (7 ^ 2 + 8)) / 2 # diğer bir deyişle #, X = -7/2 + -sqrt57 / 2 #